Basic Understanding of Concept of Diathesis and Approach of Management of Diabetes Mellitus through Ayurveda - Ajai Kumar Pandey; Krishana Bihari; Tanmay Nigam; Shivani Chauhan; Kapil (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
Prediabetes & diabetes mellitus (DM) is one of the major metabolic disorders in which faulty lifestyle play significant role in the genesis as well as diathesis of this disease. Recent years have shown significantly rising trend of Prediabetes and diabetes mellitus all over the world. It is a serious medical condition and considered as grey area between normal one and diabetes mellitus. Worldwide more than 300 million people are at increased risk of developing diabetes mellitus but they are unaware of it. American Diabetic Association (ADA) on 27th march, 2002 gave the term Prediabetes. Such types of patients are at risk for not only developing Type-2 Diabetes mellitus, but also risk for macro & micro-vascular complications. The progression into diabetes mellitus from Prediabetes is approximately 25% over 3 to 5 years. It is amazing that 7 century B.C. Ayurvedic texts have been vividly described the etio-pathogenesis, classification, prognosis, complication and management of prediabetes and diabetes with highly evolved manner, which is well comparable to the latest development in this field. At one side, Ayurveda conceived the idea of high caloric diet and sedentary habit as important causative factors for Apathyanittaja Prameha and other side genetic/hereditary factors for Sahaja/Jata Prameha. The primary one is very similar to prediabetes and Type-2 diabetes mellitus of conventional biomedical science. The patients of Prameha are believed to possess impaired Agni and depleted Ojas status i.e. hypo-metabolic and immunocompromised state. At present, the primary goal is not only to achieve euglycemia but also to minimize its further progression to type-2 DM and its associated complications. The management of prediabetes is still evolving in the biomedical science. In-spite of many advances in the understanding and management of prediabetes & DM and its consequences remains unsatisfactory and challenging. This seeks great attention from the present-day practitioners and researchers to evaluate the present status of this mega health event. Thus, the present concept will provide a new lead to the understanding of prediabetes & DM and its management through Ayurveda.